ISTILAH PERTUKANGAN DALAM BAHASA BALI (Perspektif Kata dan Proses Pembentukan Kata dalam Upaya Penguatan Prodi Sastra Agama dan Pendidikan Bahasa Bali) - I Made Suweta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
The terms of the Balinese language in carpentry need to be known again by the people ofBali. It aims to make Bali Language users not extinct. By knowing the terms in this carpentheBalinese language at least contribute in preserving and mengajegkan Balinese language itself.To understand every term that is in carpentry activities it is necessary to study the morphologysystem, in order to know the meaning and purpose of the word. For that in this paper there aresome issues that need to be studied namely: (1) What are the basic Balinese word form in carpentryterms? and (2) How is the system of word formation (morphology) of Balinese in terms ofcarpentry? The theory used in this study is the structural theory of language that emphasizes onthe level of form (signifiant) and meaning (signify). There are pu methods in the discovery ofdata used literature study done by listening to the terms of carpentry in the sources of literaturerelated to the term in the carpentry language of Bali. Based on the study in this paper, foundsome kind of vocabulary of the term carpentry. In addition to the vocabulary in basic form, alsofound some vocabulary of the term carpentry that experienced the process of formation of newwords through morphological process through affixation, pluralism, and re-word.